Genomic aberrations in early stage human hepatocellular carcinomas - Hisaki Nagai (2018)
BACKGROUND. Primary liver cancer, which most often takes the form of hepatocellular carcinoma (HCC), is among the 10 most common cancers in humans worldwide. In hepatocarcinogenesis, evidence of a multistep process is supported by the marked increase of HCC incidence with age; most HCCs are diagnosed in the second half of life, generally after a long period of chronic liver disease and in frequent association with cirrhosis. This long process may be correlated with the development of multiple genetic lesions, the origin of which currently remain largely unknown. In a previous study, the authors collected data on genomic DNA aberrations in primary HCC by restriction landmark genomic scanning (RLGS), a powerful screening method for the human genome. METHODS. The authors examined the genomic aberrations that occurred in early stage HCCs by means of RLGS of NotI-cleaved and32P-end- labeled genomic DNA resolved by electrophoresis in a two-dimensional gel. More than 2000 radioactive spots originating from NotI cleavage sites were compared among six small HCC nodules and their normal counterparts. RESULTS. The intensities of five spots were consistently higher in the small HCCs, and the same effect was observed in large HCCs. In addition, the intensities of 22 spots were consistently half those of normal tissue, suggesting the loss of one allele. CONCLUSIONS. The occurrence of certain genomic alterations in early stage HCCs, as reflected by an increase or decrease in spot intensity, seems to reflect early events that occur during HCC development.